THE ANALYSIS OF THE INFLUENCE OF FINANCIAL PERFORMANCE AND PERFORMANCE TOWARDS FINANCIAL INDEPENDENCE OF CENTRAL GENERAL HOSPITALS WITH THE STATE DEPENDENCE AS A MODERATING IN THE PUBLIC SERVICES AGENCY OF THE MINISTRY OF HEALTH - Sirait, Sri Wahyuni (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was toexamineandtoanalyze ofhealth serviceperformanceBed Occupancy Ratio (BOR), Turn Over Interval (TOI) and Average long Of Stay (Avlos)and Finance performance (Current ratio, Quick Ratio, Solvability Ratio, Rentability Ratio) which influenced hospital Independency fund and to examine moderating variable in the in Central General Hospital BLU Health Ministeryin the period of 2013-2015.Theresearch used causality method with the population of 13 hospitals, and all of them were used as thesamples, taken by using census sampling technique so that there would be 39 observation samples to be analyze.  The  of the research showed that health serviceperformance(BOR, TOI dan Avlos) and Finance Performance (Current Ratio, Quick Ratio, Solvabilitas Ratio and Rentabilitas Ratio)had significant influence on dependency of Government fundof hospital. Partially,onlyRentablitas Ratiohas positive and significant influence onhospital financialindependency, butthe other variabledid not have any significant influence on Hospital FinancialIndependency. Based on the result of residual, this research showed that dependency of Government funddid not moderate the relationship amonghealth serviceperformance (BOR, TOI, Avlos) and Finance performance (Current ratio, Quick Ratio, Solvabilitas Ratio, Rentabilitas Ratio)on hospital financialindependency.